Assembly mechanism and co-occurrence patterns of DNRA microbial communities and imprint of nitrate reduction in the Songhua River sediments of China's largest old industrial base. (15th November 2022) - Zhao, Yiyi; Yuan, Fang; Li, Shaoyong; Zhang, Jinpeng; Li, Yuze; Shi, Xiang; Yang, Jiachun; Ni, Shou-Qing; Ismail, Sherif
Abstract: Dissimilatory nitrate reduction to ammonium (DNRA) reduces nitrate to ammonium nitrogen instead of nitrogen gas, which is an important internal linking process of nitrogen cycle. No literature has reported the assembly mechanism of DNRA microbial communities. Here, the deep assembly mechanisms and co-occurrence patterns of DNRA microbial communities and imprint of nitrate reduction in Songhua River Basin (an inland river located in northeastern China) were studied. The DNRA potential rates were detected at six sampling sites, ranging from 0.25 ± 0.23 to 4.22 ± 0.61 μmol N/L/h, accounting for 33.07% to 98.08% of the total nitrate reduction. Spearman analysis indicated that the nrfA gene abundance was significantly positively correlated with the concentration of total nitrogen (TN) in sediments ( p  < 0.05), suggesting that nutrient inputs may enhance the metabolic potential of DNRA bacteria. Co-occurrence network and Spearman correlation analyses showed that the DNRA rates were significantly correlated with the abundance of keystone species, but not with the dominant genera ( p  < 0.05). Variance partitioning analysis (VPA) revealed that sediment physicochemical properties and spatial factors explained only 21.07% and 14.51% of the DNRA community variation. Null model and neutral community model both revealed stochastic processes play a major role in shaping DNRA microbial community structure. The drift was the most important process, explaining 36.36% of the community variation, followed by homogeneous selection and homogenizing dispersal, which accounted for 27.27% and 22.73%, respectively. Additionally, Geobacteraceae played an important role in DNRA and the entire bacterial community in Songhua River. This study explored the underestimated DNRA process and the deep community assembly mechanisms, which will contribute to understanding nitrate conversion and the impact of nitrogen pollution on microbial communities of river sediments in cold regions. Graphical abstract: Image 1 Highlights: DNRA potential rates were detected at six sites among 12 sampling sites. DNRA abundance and rates were significantly correlated with keystone species. Stochastic processes play an important role in shaping DNRA community structure. Geobacteraceae was important keystone member in DNRA and total bacterial community.